Developing Intercultural Communicative Competence in Local ELT - Beresova, Jana (Spectrum Slovakia series, 2019)
Language and culture relate to each other. It is important to refine teaching processes to enable language learners to use target languages effectively. This book shows that language and culture should be viewed in their interrelationship as they have a significant impact on the naturalness and appropriateness of discourse.